COVID-19 in Renal Transplant Patient Presenting With Active Typical Symptoms and Resolved Atypical Symptoms - Sreedhar Adapa MD, FACP, FASN; Venu Madhav Konala MD, FACP, CACP; Srikanth Naramala MD, FACR, CCD; Subba Rao Daggubati MD; Narayana Murty Koduri MD, MRCPsych; Vijay Gayam MD; Avantika Chenna MD, FASN (SAGE Publishing, 2020)
The novel coronavirus disease has brought the world to standstill with high infectivity and rapid transmission. The disease caused by novel coronavirus is termed as coronavirus disease 2019 (COVID-19). We present the case of a renal transplant patient who was infected with COVID-19 through community spread and presented with fever and gastrointestinal symptoms. Transplant recipients are particularly vulnerable because of the immunosuppressed state. These patients can shed a virus for a prolonged period and can have a higher load of the virus. There have been no COVID-19 cases transmitted through organ donation. Preinfection immunological impairment can aggravate the severity of the infection. The transplant team plays a crucial role in donor and recipient evaluation and guiding the timing of the transplant. Although specific published data are lacking with regard to transplant recipients, they should follow the same precautions as the general population, like avoiding nonessential travel and practice social distancing.